2014
DOI: 10.1246/cl.140704
|View full text |Cite
|
Sign up to set email alerts
|

New Magnesium-ion Conductive Electrolyte Solution Based on Triglyme for Reversible Magnesium Metal Deposition and Dissolution at Ambient Temperature

Abstract: New electrolyte solutions for rechargeable magnesium metal batteries were studied. The electrolyte solution composed of triethylene glycol dimethyl ether (triglyme) and butyl methyl triglyme as solvents and magnesium(II) bis(trifluoromethanesulfonyl)amide as a magnesium salt. The reversible deposition and dissolution of magnesium metal was achieved in these electrolyte solutions at ambient temperature. The electrochemical stability of triglyme-based electrolyte solutions showed high stability toward oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 20 publications
6
75
0
Order By: Relevance
“…According to the above definition, the decomposition potential of the 0.5 mol dm -3 Mg(Tf 2 N) 2 /G3 solution locates at around +3.4 V vs. Mg QRE with the same sweep rate. 19 Such an improvement in anodic stability due to a lack of free glymes has also been reported in LiTf 2 N/glyme solution. 20 Therefore, it is concluded that the IL/glyme mixtures have higher anodic stability than the IL-free Mg(Tf 2 N) 2 /G3 solution.…”
Section: 19mentioning
confidence: 60%
See 4 more Smart Citations
“…According to the above definition, the decomposition potential of the 0.5 mol dm -3 Mg(Tf 2 N) 2 /G3 solution locates at around +3.4 V vs. Mg QRE with the same sweep rate. 19 Such an improvement in anodic stability due to a lack of free glymes has also been reported in LiTf 2 N/glyme solution. 20 Therefore, it is concluded that the IL/glyme mixtures have higher anodic stability than the IL-free Mg(Tf 2 N) 2 /G3 solution.…”
Section: 19mentioning
confidence: 60%
“…The viscosity of each glyme mixture is about 25-26 mPa s, one order of magnitude higher than that of the previously reported glyme-rich mixture (2.32 mPa s; Mg 2+ :IL:G2 = 1:7:56 by mole). 16 However, the conductivities shown in Table III 16,17,19 although slightly smaller than typical lithium-ion conductive electrolyte solutions. Notably, the bulk bath properties were fairly similar within 7 days for each IL/glyme mixture (see Fig.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations